Impact of foreign aid on governance - CHANG, Hana (KDI School, 2015)
The development literature has long examined the relationship between foreign aid and governance with a focus on Africa, employing governance indicators such as the ‘rule of law’ and ‘corruption,’ mainly from the ICRG (International Country Risk Guide). This study suggests a different approach with wider variance in the governance indicators and from the conventional focus on the African region. The study looks at the level of aid as a share of GNI in 16 former Spanish colonies in Latin America from 1999 to 2013, and assesses its impact on the region’s governance qualities. The six governance indicators adopted in this study are (i) accountability, (ii) transparency, (iii) rule of law, (iv) government effectiveness, (v) regulatory quality, and (vi) political stability. The empirical findings from this study present some interesting results, and leave an implication that aid alone is not enough; aid should be complementary to other policy measures to combat the social, economic, and political structural barriers that hinder development as a whole, in particular the quality of governance in the Latin America.
Thesis(Master) --KDI School:Master of Development Policy,2015